Wither NBFCS in India? - Prakash, S. Ravi; Krishna Reddy, K.; Chary, T. Satyanarayana (Indian Journal of Marketing, 2005)
Non-Banking Financial Companies (NBFCs) 1 are the concerns rendering financial services similar to commercial banks and financial institutions, but do not qualify to be branded as banks, entered Indian Financial System in a big way to increase resources to Indian corporate world during 80s due to frequent credit squeezes cash crunches and laborious procedures with Financial Institutions and commercial banks. Based on their nature, NBFCs can be grouped into different types as Loan and Finance Companies, Investment Companies, Hire-purchase Finance Companies, Equipment Leasing Companies, Mutual Benefit Financial Companies, Housing Finance Companies and Residuary Non Banking Companies.